Strategi Tata Tertib Sekolah dalam Membentuk Perilaku Siswa yang Disiplin di SMA Islam Nusantara - Moh Tabarok; Deden Indra; Rahmad Idea Tribisono; Rulam Ahmadi; Ifit Novita Sari (Jurnal Simki Postgraduate, 2024)
This study aims to assess the efficacy of the SMA Islam Nusantara Strategy in cultivating students' character traits of discipline and responsibility, as manifested through school regulations. Educational institutions aspire to objectives beyond mere academic excellence, graduation rates, or admission to prestigious institutions. More profoundly, schools strive to mold students with elevated morality and integrity, aligned with the principles of akhlakul karimah. The school regulations, akin to the operant conditioning theory postulated by B.F. Skinner, serve as a tangible manifestation of behavioral conditioning. Employing a field research approach, this study involves continuous direct observation by researchers throughout the entire investigative process. The strategy for instilling student discipline through the enforcement of school regulations encompasses the following activities: a) Habituation; b) Conditioning; c) Spontaneous activities. The student counseling guidance book serves as concrete evidence of the disciplinary formation through rule implementation at SMA Islam Nusantara, documenting applied regulations and the names of rule-violating students. It is anticipated that this research will significantly contribute to informing and supporting the implementation of school regulations as a strategic approach for shaping student disciplinary conduct. Specifically, it aims to provide deeper insights into the effectiveness of school regulations in fostering and sustaining disciplined student behavior within the educational milieu.